Proposing a modified system based on recovery of preset pressurization energy in the integrated pumped-hydro and compressed gas energy storage system - Amin Hadidi (Results in Engineering, 2025)
Today, the pumped-hydro combined with compressed gas (PHCG) method is an effective and efficient method for power plant energy storage. The most important disadvantage of this system is its low efficiency compared to the conventional method of water pumping-based energy storage. Therefore, in this study, this energy storage method has been modified. For this purpose, the energy spent to create pressure inside the system's high-pressure container is recovered in the discharge stage. This modification prevents energy losses in the storage system and consequently, enhances its efficiency, considerably. To demonstrate the effective performance of the modified system, the performance of both systems was investigated for the storage of generated energy in the 10 MW Khaf wind farm in Iran as a case study. The research results showed that by using the modified system, the efficiency of the energy storage system enhances from 37.12 % to 72.83 %. Also, the efficiency of the modified system is independent of the preset pressure and the liquid to gas ratio in the high-pressure container, while the effectiveness of the PHCG is strongly dependent on the values of these two parameters.